Valoração ambiental: uso do método dose-resposta na mensuração do impacto na lucratividade da produção de arroz irrigado na microrregião de Formoso do Araguaia-TO - Wakim, Vasconcelos Reis (Universidade Federal do Tocantins, 2016)
The environmental valuation is a tool used to measure the environmental impacts and to quantify the environmental goods. Currently there are several models of environmental valuation, such as: dose-response, contingent valuation, among others who use specific techniques to value the natural resource as well as the impact on the environment. The objective of this study is to measure the impact on the profitability of rice production in irrigated Microregion Formoso do Araguaia, state of Tocantins, which consists the cities of Lagoa da Confusão, Dueré, and Formoso do Araguaia, If changes occur in water availability. Were simulated two scenarios: one optimistic and another pessimistic, whose variables: planted area, sales price and cost price remained constant, varying only the variable water availability. In the optimistic scenario the variable water availability was set to 8.49 m3/h/hectare in the pessimistic scenario and water availability was defined as 0.87 m3/h/hectare. We used the Monte Carlo method, with a total of 10,000 interactions, such as statistical tool to determine the Probability Density Function of Total Income and therefore determine the probability of the outcome in each proposed scenario. In the optimistic scenario, after the simulation we obtained an average profit of $ 29.7 million reais. The estimated profit at this stage was in class (R$ 10,000) to R$ 10,000 with a probability of 66.78%, with the largest projected profit was R$ 47.2 million with a chance of occurrence of only 0.22%. And the smallest gain simulated by the optimistic was (R$ 49.8) million reais with a probability of 0.85%. The higher frequency of profit in the optimist was in class from R$0.00 to R$10,000 with 2866 occurrences, meaning 28.66% probability of occurrence. In the pessimistic scenario, the average profit was estimated at around R$ 22.1 million reais. The projection of the profit was in class (R$ 10,000) to R$ 10,000 with a probability of 70.85%. The highest estimated profit in this scenario was R$ 35.2 million reais with a probability of only 0.11%. The lowest value simulated in the pessimistic was (R$35.2) million with a probability of 0.09%. The higher frequency of the pessimistic profit was in class from R$0.00 to R$10,000 with 3581 occurrences, meaning 35.81% probability of occurrence. It can be concluded that there was a reduction of the average profits from the optimistic scenario tor the pessimistic scenario of about 25.6%. The reduction of the profitability of irrigated rice production can be explained by the emergence of diseases in the rice fields, for example, the panicle blast, lack of water is by long periods of drought and the great competition by use of waters. In the simulation results, it appeared that only the variable water is not sufficient to explain the reduction in profit of rice production in irrigated Microregion Formoso do Araguaia, Tocantins, being necessary to use other variables in the swing model. Therefore, we must conduct further studies to see what other variables, besides water availability, can influence the reduction or increase in the profitability of irrigated rice production in the microregion of Formoso do Araguaia.